2020
DOI: 10.3847/2041-8213/ab6a08
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Chain Depletion of 2I/Borisov

Abstract: The composition of comets in the Solar System come in multiple groups thought to encode information about their formation in different regions of the outer protosolar disk. The recent discovery of the second interstellar object, 2I/Borisov, allows for spectroscopic investigations into its gas content and a preliminary classification of it within the Solar System comet taxonomies to test the applicability of planetesimal formation models to other stellar systems. We present spectroscopic and imaging observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
6
29
1
Order By: Relevance
“…For the visits from Nov. 1 to Dec. 21, we find colors of = 19%, 14% and 13% per 100 nm between 260 and 547 nm (α = 0.054, 0.062, 0.064). These are consistent with most published results for the same wavelength range Lin et al 2020;Guzik et al 2019), but not consistent with −8 ± 7% per 100 nm reported by Kareta et al (2020). If the dust color is assumed to be constant during the short observation campaign, reddening can be considered as its mean value, 15%.…”
Section: Water Production Ratessupporting
confidence: 88%
“…For the visits from Nov. 1 to Dec. 21, we find colors of = 19%, 14% and 13% per 100 nm between 260 and 547 nm (α = 0.054, 0.062, 0.064). These are consistent with most published results for the same wavelength range Lin et al 2020;Guzik et al 2019), but not consistent with −8 ± 7% per 100 nm reported by Kareta et al (2020). If the dust color is assumed to be constant during the short observation campaign, reddening can be considered as its mean value, 15%.…”
Section: Water Production Ratessupporting
confidence: 88%
“…We note the non-detection of C2 lines could be due to our shallow spectrum, or because the comet is at lower activity at this epoch; the surface activity could increase significantly as it approaches perihelion. We note that our independent spectroscopic observations lead to the results similar to [7,14,15]. To summarize, both imaging and spectroscopy show that 2I/Borisov shares similar properties with comets in the solar system, hence it is unremarkable except for it being ejected from another star.…”
Section: Resultssupporting
confidence: 67%
“…However, the prediscovery photometry may also be compatible with CO 2 -driven activity where CO 2 can become active at >13 au (Womack et al 2017;Ye et al 2020). As discussed in Section 3.4, a significant production rate of H 2 O is inferred from the observed production of CN and C 2 gas (Fitzsimmons et al 2019;Kareta et al 2020) and is ∼100 kg s −1 comparable, though larger than the H 2 O∼20 kg s −1 production inferred from the detection of the [O I] 6300 Å line taken at further heliocentric distances (McKay et al 2020). Since our photometric light curve suggests that the activity of 2I is partially driven by CO, we expect the mass loss of CO to also be much higher than the mass loss from dust in the ∼10-100 kg s −1 range as it approaches perihelion.…”
Section: Long-term Light Curve and Volatile-driven Activitymentioning
confidence: 78%
“…The second ISO, 2I, seems on all accounts like an ordinary comet compared to the comets of the solar system, though it is depleted in some chemical species relative to solar system comets (Kareta et al 2020;Opitom et al 2019;Bannister et al 2020) and has an excess of CO (Bodewits et al 2020;Cordiner et al 2020). If it were not for its significantly hyperbolic orbit, 2I probably would not have warranted an in-depth scientific investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation